2009
DOI: 10.1002/eji.200838978
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial RNA is recognized by different sets of immunoreceptors

Abstract: Innate immunity recognizes microbial nucleic acids by endosomal TLR and cytosolic recognition systems. Despite increasing knowledge on the properties of nucleic acid recognition for viral RNA and bacterial DNA, little is known about the immunogenicity of prokaryotic RNA. Here we show that bacterial RNA is a potent trigger for type-I IFN secretion in human PBMC. Activation of human plasmacytoid dendritic cells was dependent on endosomal maturation and could be blocked by a TLR7-specific inhibitor. Murine plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 40 publications
1
92
0
Order By: Relevance
“…pDCs are professional producers of type I IFN and are equipped with a limited set of innate immune receptors, including TLR7 and TLR9. Experiments with FLT3L-generated murine pDCs demonstrated that IFN-a production upon bacterial RNA stimulation was abolished in TLR7-deficient pDCs (28,34). Similar results were observed in human pDCs in which TLR7 expression was silenced by small interfering RNA (siRNA) (32).…”
Section: Tatjana Eigenbrod and Alexander H Dalpkementioning
confidence: 61%
See 2 more Smart Citations
“…pDCs are professional producers of type I IFN and are equipped with a limited set of innate immune receptors, including TLR7 and TLR9. Experiments with FLT3L-generated murine pDCs demonstrated that IFN-a production upon bacterial RNA stimulation was abolished in TLR7-deficient pDCs (28,34). Similar results were observed in human pDCs in which TLR7 expression was silenced by small interfering RNA (siRNA) (32).…”
Section: Tatjana Eigenbrod and Alexander H Dalpkementioning
confidence: 61%
“…Similarly, both human PBMCs and murine bone marrow-derived macrophages (BMDMs) responded to intracellular delivery of total bacterial RNA with TNF production (27)(28)(29)(30). In addition to inducing classical NF-kB-dependent cytokines, bacterial RNA has been identified as a strong trigger of IFN-a in plasmacytoid dendritic cells (pDCs) and of IFN-b in myeloid dendritic cells (mDCs) in an IRF-dependent manner (28,(30)(31)(32)(33)(34). Depending on the model system, the involvement of IRF1, IRF3, IRF5, or IRF7 has been implicated (30,31,33,35).…”
Section: Tatjana Eigenbrod and Alexander H Dalpkementioning
confidence: 99%
See 1 more Smart Citation
“…Although the critical roles for bacterial DNA and viral RNA in the induction of innate immune responses have been acknowledged for long time, the importance of bRNA recognition has only recently started to be unraveled. It was demonstrated that intracellular delivery of bRNA induced secretion of type I IFNs, as well as proinflammatory cytokines, including TNF, IL-12p40, or IL-1b (10,(14)(15)(16)(17). In plasmacytoid DCs, bRNA-induced production of type I IFNs is mediated by TLR7 (15), whereas the murine receptor TLR13 was identified only recently to sense bRNA in both bone marrow-derived macrophages (BMDMs) and DCs by recognizing a unique nucleotide motif present in the bacterial 23S rRNA (18,19).…”
mentioning
confidence: 99%
“…It was demonstrated that intracellular delivery of bRNA induced secretion of type I IFNs, as well as proinflammatory cytokines, including TNF, IL-12p40, or IL-1b (10,(14)(15)(16)(17). In plasmacytoid DCs, bRNA-induced production of type I IFNs is mediated by TLR7 (15), whereas the murine receptor TLR13 was identified only recently to sense bRNA in both bone marrow-derived macrophages (BMDMs) and DCs by recognizing a unique nucleotide motif present in the bacterial 23S rRNA (18,19). Activation of TLR13 triggers the recruitment of the common TLR adapter molecule MyD88, resulting in activation of NF-kB and transcription of NF-kB-dependent cytokines (19).…”
mentioning
confidence: 99%